Hop/Sti1 – A Two-Faced Cochaperone Involved in Pattern Recognition Receptor Maturation and Viral Infection - Lamm, Christian E.; Kraner, Max. E.; Hofmann, Jörg; Börnke, Frederik; Mock, Hans-Peter; Sonnewald, Uwe (Frontiers in Plant Science, 2017)
Perception of pathogens by host pattern recognition receptors (PRRs) or R proteins is a prerequisite to promote successful immune responses. The Hsp70/Hsp90 organizing protein Hop/Sti1, a multifunctional cochaperone, has been implicated in the maturation of a receptor-like kinase (RLK) necessary for chitin sensing. However, it remains unknown whether Hop/Sti1 is generally participating in PRR genesis. Using RNA-interference (RNAi), we silenced Hop/Sti1 expression in Nicotiana tabacum to gain further insight into the role of the cochaperone in plant defense responses. As expected, transgenic plants do not respond to chitin treatment anymore. In contrast to this, trafficking and functionality of the flagellin PRR FLS2 were unaltered, suggesting a selective involvement of Hop/Sti1 during PRR maturation. Furthermore, Hop/Sti1 was identified as a cellular determinant of potato virus Y (PVY) symptom development in tobacco, since PVY was able to accumulate to near wild-type level without provoking the usual veinal necrosis phenotype. In addition, typical antiviral host defense responses were suppressed in the transgenic plants. These data suggest that perception of PVY is dependent on Hop/Sti1-mediated receptor maturation, while viral symptoms represent a failing attempt to restrict PVY spread. In addition, Hop/Sti1 colocalized with virus-induced membrane aggregates in wild-type plants. The retention of Hop/Sti1 in potential viral replication complexes suggests a role during viral translation/replication, explaining why RNAi-lines do not exhibit increased susceptibility to PVY. This study provides evidence for a dual role of Hop/Sti1 in PRR maturation and pathogen perception as well as in promoting viral proliferation.